A novel source of atomic hydrogen for passivation of defects in silicon (Phys. Status Solidi RRL 5/2017). Issue 5 (May 2017) - Hamer, Phillip; Bourret‐Sicotte, Gabrielle; Martins, George; Wenham, Alison; Bonilla, Ruy S.; Wilshaw, Peter
Abstract : It is well established that atomic hydrogen can be used to passivate surface and bulk defects in crystalline silicon. There are an increasing number of devices, including advanced solar cell structures, where it is desirable to introduce hydrogen while avoiding the use of dielectric layers and damage from plasma sources. The cover image (cf. article no.1770327 by Hamer et al.) shows a holder for a thin palladium leaf, which when inserted between a hydrogen containing plasma and a silicon sample, allows for exposure of the sample to significant atomic hydrogen while avoiding any damage that would otherwise be generated by the plasma. Atomic hydrogen production was detected through the deactivation of boron in silicon and the improvement in the surface passivation provided at silicon/oxide interfaces. The release of significant atomic hydrogen from this metallic leaf is somewhat surprising in view of the large body of literature observing dominant recombinative desorption of hydrogen at such surfaces. This process has been dubbed shielded hydrogen passivation and opens up exciting possibilities for in‐line exposure of samples to atomic hydrogen, using a metallic shield to separate the sample and hydrogen source chambers.